AI techniques for reliability prediction for electronic components - Bhargava, Cherry, 1982- (Advances in computational intelligence and robotics (ACIR) book series., 2020)
"This book explores the theoretical and practical aspects of prediction methods using artificial intelligence and machine learning in the manufacturing field"--